Computing legacies digital cultures of simulation - Krapp, Peter 1970- (The MIT Press, 2024)
"Krapp explores how simulation merges with a variety of institutions and media, including games, music, museums, and universities
Keywords: COMPUTERS / Computer Simulation; COMPUTERS / History; SOCIAL SCIENCE / Media Studies; Computer simulation / Social aspects; Digital media / Social aspects; Computers and civilization; Ordinateurs et civilisation